The effects of gift vouchers and environmental certificates on the demand for a collective DRT system - Aljoscha Minnich; Holger A. Rau; Jan Christian Schlüter (Transportation, 2021)
This paper analyzes in a large-scale field experiment (N = 1425) whether gift vouchers stimulate the use of a demand responsive transportation (DRT) system. This scenario is compared to a situation where customers receive environmental certificates, which report the saved carbon dioxide as a consequence of the bus ride. In our two treatments, the gift vouchers and the environmental certificates could be gained by reaching to a certain threshold of rides with the DRT service (EcoBus). We find that the demand went up more by gift vouchers (83%) compared to certificates (65%). The data show that vouchers especially outperform the certificates at the end of the treatment phase.
Keywords: C93; D12; D83; D91; 380; Demand responsive transport; Field experiment; Incentive effects